Political and Democratic Role of The National Party in Restoring Peace and Democracy in Balochistan During the Insurgency - Naheed, Kishwar; Shinwari, Rizwan Ali (Pakistan Journal of Humanities and Social Sciences, 2023)
Balochistan is a troubled province in the country since the inception of Pakistan in 1947. The political turmoil is deeply embedded in the process of princely states joining the newly established Pakistan. Political parties including the National Party tried to curb the situation and pave the way for a peaceful reconciliation between the marginalized people of Balochistan and the state of Pakistan. The National Party (NP) is one of the bigger mass political parties in the province. It is a social-democratic and center-to-the-left party whose legacy party is linked back to the Kalat State’s National Party. In 2003, the merger of two political parties, the Balochistan National Democratic Party (BNDP) of Mir Hasil Khan Bizenjo, and the Balochistan National Movement (BNM) of Abdul Hayee Baloch led to the foundation of this popular mass political party. The Baloch people have been denied their political, economic, and cultural rights. They also ignored their right to self-governance and the management of their region's natural resources, ever since Pakistan was founded. Balochistan was not represented at the state level and had little influence over how the government was run. The focus of this paper is to know about the role of the National Party in restoring peace after the insurgency and how the leadership of the National Party did an effort to bring back democracy in the province to keep the federation of Pakistan. The research is a qualitative study based on primary and secondary data collected by researchers. Primary data was collected from the key informants of political parties. The secondary data includes an analysis of the written literature of the parties. It is concluded that the role of such parties in the establishment of peace and reconciliation between the state and the people of the province is important for the prosperity of the people of Balochistan in particular, and Pakistan in general.